A Review on Artificial Intelligence Methodologies for the Forecasting of Crude Oil Price. Issue 3 (2nd July 2016) - Chiroma, Haruna; Abdul-kareem, Sameem; Shukri Mohd Noor, Ahmad; Abubakar, Adamu I.; Sohrabi Safa, Nader; Shuib, Liyana; Fatihu Hamza, Mukhtar; Ya'u Gital, Abdulsalam; Herawan, Tutut
Abstract: When crude oil prices began to escalate in the 1970s, conventional methods were the predominant methods used in forecasting oil pricing. These methods can no longer be used to tackle the nonlinear, chaotic, non-stationary, volatile, and complex nature of crude oil prices, because of the methods' linearity. To address the methodological limitations, computational intelligence techniques and more recently, hybrid intelligent systems have been deployed. In this paper, we present an extensive review of the existing research that has been conducted on applications of computational intelligence algorithms to crude oil price forecasting. Analysis and synthesis of published research in this domain, limitations and strengths of existing studies are provided. This paper finds that conventional methods are still relevant in the domain of crude oil price forecasting and the integration of wavelet analysis and computational intelligence techniques is attracting unprecedented interest from scholars in the domain of crude oil price forecasting. We intend for researchers to use this review as a starting point for further advancement, as well as an exploration of other techniques that have received little or no attention from researchers. Energy demand and supply projection can effectively be tackled with accurate forecasting of crude oil price, which can create stability in the oil market.